The Aesthetics of Islamic Literature: Lesson Learned from Forum Lingkar Pena - Aries Adenata; Titis Srimuda Pitana; Dwi Susanto (Karsa: Journal of Social and Islamic Culture, 2018)
This study is to illustrate of the Islamic literature discourse. In the history of modern literature in Indonesia has always appeared Islamic works. But the presence of Islamic literature was deliberately rejected. Even the debate about the Islamic literary discourse occurred in several periods of Indonesian literature. The presence of the aesthetic discourse of Islamic literature between accepted and rejected. One party, assuming that Islamic literature is the same presence as others, for example Hindu literature also exists and is present in the Indonesian literary universe. While others say literature is a literature that does not need to be labeled.